Discussion on islamic finance and small medium enterprises’ financial accessibility - Mohd Thas Thaker, Hassanudin *; Chandra Sakaran, K. (State Islamic University (UIN) Syarif Hidayatullah Jakarta, 2019)
This study attempts to provide some understanding of SMEs’ access to finance in Malaysia using Islamic finance and its successfulness. The innovation that taking place in the Malaysia financial landscape has benefits the SMEs in accessing financial assistance without relying on the traditional mode of financing. The role of government of Malaysia is also undisputable in supporting the progression of SMEs via various policy implementation. Apparently, in the context of Indonesia, the role SMEs is also undeniable in boosting up the growth of Indonesian economy. Statistically speaking, SMEs in Indonesia represent about 99 percent in all economic sector and involved labor participation of almost 95 percent. Although the contributions are wider, the issue of financial accessibility still becomes one of the main hurdles that block the development of SMEs in Indonesia. Therefore, the present study has used content analysis to critically look at the success of SMEs financing in Malaysia based on Islamic financing provides some recommendations based on Malaysian SMEs financing successfulness for Indonesian authority to further restructure and enhance their existing financial assistance to the SMEs based on Islamic financing.